EURASIP Journal on Bioinformatics and Systems Biology - Serpedin, Erchin
The overall aim of EURASIP Journal on Bioinformatics and Systems Biology is to publish research results related to signal processing and bioinformatics theories and techniques relevant to a wide area of applications into the core new disciplines of genomics, proteomics, and systems biology. The journal is intended to offer a common platform for scientists from several areas including signal processing, bioinformatics, statistics, biology and medicine, who are interested in the development of algorithmic, mathematical, statistical, modeling, simulation, data mining, and computational techniques, as demanded by various applications in genomics, proteomics, system biology, and more general in health and medicine. Articles should emphasize original results related to the theoretical and algorithmic aspects of signal processing and bioinformatics, in close connection with the applications to genomics, proteomics, systems biology and medicine. Tutorial articles, especially those emphasizing strong components of signal processing or bioinformatics in multidisciplinary views of genomics, proteomics and systems biology are also welcome. Review and tutorial (overview) style articles dealing with software and databases presentations are welcomed provided that they address important research topics and problems from the fields of bioinformatics, genomics, proteomics, computational neuroscience and systems biology. Short letters (or regular articles) dealing with the derivation of new results or with new derivations of well-known results of high impact in machine learning and computational statistics algorithms and that find applicability in bioinformatics and systems biology are also welcome. The journal will embrace a wide range of topics, and will accommodate different exposition styles, to help scientists with various backgrounds, e.g., engineering, bioinformatics, or biology, to interact effortlessly and to facilitate the exchange of information across the multidisciplinary areas involved. EURASIP Journal on Bioinformatics and Systems Biology employs a paperless, electronic submission and evaluation system to promote a rapid turnaround in the peer review process. The journal has been published under the open access model since 2006.